The investment function of Canadian financial institutions - Baum, Daniel Jay. (New York : Praeger, 1973)
The mutual fund has aided in bringing about the departure from single-line functions and spurred competition between different classes of institutional investors
Includes bibliographical references.
osc 06/09/2019
Loans
Keywords: Mutual funds; Bank investments; Pension trusts; Insurance companies